Molecular study on Pasteurella multocida and Mannheimia granulomatis from Kenyan Camels (Camelus dromedarius) - Gluecks, Ilona V.; Bethe, Astrid; Younan, Mario; Ewers, Christa; Justus Liebig University Giessen (My University, 2017)
Background: Outbreaks of a Haemorrhagic Septicaemia (HS) like disease causing large mortalities in camels (Camelus dromedarius) in Asia and in Africa have been reported since 1890. Yet the aetiology of this condition remains elusive. This study is the first to apply state of the art molecular methods to shed light on the nasopharyngeal carrier state of Pasteurellaceae in camels. The study focused on HS causing Pasteurella multocida capsular types B and E. Other Pasteurellaceae, implicated in common respiratory infections of animals, were also investigated. Methods: In 2007 and 2008, 388 nasopharyngeal swabs were collected at 12 locations in North Kenya from 246 clinically healthy camels in 81 herds that had been affected by HS-like disease. Swabs were used to cultivate bacteria on blood agar and to extract DNA for subsequent PCR analysis targeting P. multocida and Mannheimia-specific gene sequences. Results: Forty-five samples were positive for P. multocida genes kmt and psl and for the P. multocida Haemorrhagic Septicaemia (HS) specific sequences KTSP61/KTT72 but lacked HS-associated capsular type B and E genes capB and capE. This indicates circulation of HS strains in camels that lack established capsular types. Sequence analysis of the partial 16S rRNA gene identified 17 nasal swab isolates as 99% identical with Mannheimia granulomatis, demonstrating a hitherto unrecognised active carrier state for M. granulomatis or a closely related Mannheimia sp. in camels. Conclusions: The findings of this study provide evidence for the presence of acapsular P. multocida or of hitherto unknown capsular types of P. multocida in camels, closely related to P. multocida strains causing HS in bovines. Further isolations and molecular studies of camelid P. multocida from healthy carriers and from HS-like disease in camels are necessary to provide conclusive answers. This paper is the first report on the isolation of M. granulomatis or a closely related new Mannheimia species from camelids.
Keywords: pasteurellaceae; Pasteurella multocida; Mannheimia; camels; Camelus dromedarius; ddc:630